Effect of iodine impregnated plastic adhesive drapes in preventing surgical site infection post spine surgeries - Kumar, Krishan; Singh, Harpal; Dattu, Vijay; Khosla, Vaibhav; Mittal , Mandeep (International Journal of Research in Orthopaedics, 2023)
Background: Surgical Site Infection (SSI) complicates roughly 1-3% of orthopaedic surgeries. This study aimed to assess the effect of iodine impregnated plastic adhesive drapes (PAD) in preventing surgical site infection post spine surgeries. Methods: This non-randomized experimental study was conducted in the Department of Orthopedics, of a tertiary care hospital in Pathankot, Punjab, from January 1, 2022 till July 31, 2022, in which adult patients who underwent elective spine surgeries involving cervical, thoracic and lumbar spine and requiring post-operative care of at least 3 days were included. Every alternate patient received iodine impregnated surgical incise plastic adhesive drape (3M ioban 2) for draping before the skin incision. The patients were followed up on for six months after surgery. Results: It was observed a significantly higher duration of surgery in the PAD group, as compared to those without PAD (140.4±45.6 vs 112.5±36.7 mins, p value <0.05). Furthermore, length of incision was not significantly different between the two patient groups (15.4±6.6 vs 17.3±8.5 cm, p value = 0.71). It was observed that overall infection rate in our study population was 3.85% (n=3). It was found to be 3% in the patients with iodine impregnated PAD and 5% in patients without iodine impregnated PAD, with no significant difference between them (p value = 0.88). Conclusions: We found no data supporting or denying the use of iodine impregnated PAD for lowering the incidence of SSI in patients having elective spine surgery cases.